Use of microreactors and freeze-drying in the manufacturing process of chitosan coated PCL nanoparticles - Zelenková, Tereza (2018)
This paper is focused on the synthesis of chitosan-coated polycaprolactone nanoparticles in microreactors and on the freeze-drying of the nanosuspension, to separate the particles from the liquid phase. Nanoparticles were produced in the confined impinging jets mixer (CIJM) and in the multi-inlet vortex mixer (MIVM), using the solvent displacement method, with acetone or tert-butanol (TBA) as polymer solvent. The study was initially carried out considering a feed flow rate of 80 ml min−1: using acetone, the mean particle size was lower (163 ± 7 nm) and the Zeta potential was higher (31.4 ± 37 mV) with the MIVM, with respect to the CIJM (265 ± 31 nm and 9.8 ± 2.4 mV, respectively). Slightly larger particles were obtained using TBA in the MIVM (mean diameter: 221 ± 44 nm): in this case it is no longer required removing the solvent before the freeze-drying stage. The effect of the liquid flow rate was then investigated, confirming that the best results were obtained at 80 ml min−1. With respect to the freeze-drying process, the effect of lyoprotectants and of steric stabilizers on particle stability was investigated. Best results were obtained with 5% sucrose and 2.5% Poloxamer 388 (mean diameter: 306 ± 8 nm); in all cases Zeta potential remained positive and larger than +30 mV. Preliminary results about the encapsulation of a test drug, ciprofloxacin, are also shown and discussed.